Hubungan Penggunaan ChatGPT Dengan Pemenuhan Kebutuhan Mahasiswa - Muhammad Hisyam Nashir; Teddy Kurnia Wirakusumah; Dedi Rumawan Erlandia (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The rise in the phenomenon of using Artificial Intelligence such as ChatGPT and the very high trust of the Indonesian people in the development of Artificial Intelligence, especially the Gen Z generation group with Higher Education status (students), has given rise to debate in terms of the impact of its uses as a technology that helps the learning process. On the positive side, ChatGPT can provide personalized and interactive learning, while on the negative side, ChatGPT can provide incorrect and inaccurate information. Meanwhile, penetration of its uses can no longer be avoided because it is easy to access, so the good and bad sides will continue to be felt, especially for its users. Moreover, until now there is still very little research on how this technology can help fulfill the needs of students within the research campus, especially the most important need for them as someone who is pursuing higher education, namely the need for satisfying learning. Therefore, this research aims to explain the relationship between the uses of ChatGPT and the fulfillment of learning needs for students at the Faculty of Communication Sciences, Padjadjaran University with the help of the Uses and Gratification theory approach. The research method usesd is a quantitative method with a type of correlational study design using the Spearman Rank correlation test The results of this study show that there is a positive and significant relationship between the uses of ChatGPT and fulfilling the learning needs of students at the Faculty of Communication Sciences, Padjadjaran University with a correlation coefficient of 0.834. So, it can be concluded that the higher the uses of ChatGPT, the higher the fulfillment of students' learning needs, which means that frequent uses of ChatGPT can indicate that it is closely related to satisfying learning needs.